Wintertime Transport of Reactive Trace Gases From East Asia Into the Deep Tropics. Issue 22 (19th November 2018) - Donets, Valeria; Atlas, E. L.; Pan, L. L.; Schauffler, S. M.; Honomichl, S.; Hornbrook, R. S.; Apel, E. C.; Campos, T.; Hall, S. R.; Ullmann, K.; Bresch, J. F.; Navarro, M.; et al.
Abstract: Unprecedented growth of East Asian economies has led to increases of anthropogenic pollutants in the regional atmosphere. This pollutant burden is transported into the global atmosphere and is a significant source of intercontinental and transboundary anthropogenic pollution. This work analyzes pollution transport into the western Pacific associated with the dispersion of East Asian pollution during Northern Hemisphere winter. To examine transport characteristics, we use chemical and dynamical data sets obtained during the CONvective TRansport of Active Species in the Tropics ( CONTRAST ) field campaign, conducted from Guam during January–February 2014. We identify that the evolution of shear lines from decaying cold fronts and their southward advancement facilitates polluted air transport into low latitudes of the Western Pacific Ocean. Observations from two cases of shear line passage are analyzed. The result shows that this transport process significantly elevates anthropogenic trace gases in the marine boundary layer and lowermost free troposphere up to 3–4 km. Results of our analysis show that chemical influence of the shear line on the background tropical marine atmosphere varies as a function of pollution source, intensity, shear line strength, and the speed of advancement, as well as local background conditions. To quantify the contribution of shear‐line‐related transport, we introduce an index, the Anthropogenic Enhancement Factor ( AEF ), defined as a fractional change in mixing ratio of a gas brought about by the advancing front. This index shows that the most significant enhancements are for species with photochemical lifetimes comparable to their transport times from source regions. Key Points: Elevated levels of anthropogenic trace gases transported in the lower atmosphere from East Asia were found behind shear lines in the deep tropical West Pacific during winter The chemical impact of the pollutants associated with the shear line depends on source strength, shear line organization, speed of advancement, and background conditions Anthropogenic Enhancement Factor is a metric developed to quantify the chemical impact of the air behind the shear line on the local background conditions